Denosumab in patients with giant-cell tumour of bone: a multicentre, open-label, phase 2 study. Issue 12 (December 2019) - Chawla, Sant; Blay, Jean-Yves; Rutkowski, Piotr; Le Cesne, Axel; Reichardt, Peter; Gelderblom, Hans; Grimer, Robert J; Choy, Edwin; Skubitz, Keith; Seeger, Leanne; Schuetze, Scott M; Henshaw, Robert; et al.
Summary: Background: Giant-cell tumour of bone (GCTB) is a rare, locally aggressive osteoclastogenic stromal tumour of the bone. This phase 2 study aimed to assess the safety and activity of denosumab in patients with surgically salvageable or unsalvageable GCTB. Methods: In this multicentre, open-label, phase 2 study done at 30 sites in 12 countries we enrolled adults and skeletally mature adolescents (aged ≥12 years) weighing at least 45 kg with histologically confirmed and radiographically measurable GCTB, Karnofsky performance status 50% or higher (Eastern Cooperative Oncology Group status 0, 1, or 2), and measurable active disease within 1 year of study enrolment. Patients had surgically unsalvageable GCTB (cohort 1), had surgically salvageable GCTB with planned surgery expected to result in severe morbidity (cohort 2), or were enrolled from a previous study of denosumab for GCTB (cohort 3). Patients received 120 mg subcutaneous denosumab once every 4 weeks during the treatment phase, with loading doses (120 mg subcutaneously) administered on study days 8 and 15 to patients in cohorts 1 and 2 (patients in cohort 3 did not receive loading doses). The primary endpoint was safety in terms of the type, frequency, and severity of adverse events; secondary endpoints included time to disease progression from cohort 1 and the proportion of patients without surgery at month 6 for cohort 2. The safety analysis set included all enrolled patients who received at least one dose of denosumab. This study is registered with ClinicalTrials.gov, number NCT00680992, and has been completed. Findings: Between Sept 9, 2008, and Feb 25, 2016, 532 patients were enrolled: 267 in cohort 1, 253 in cohort 2, and 12 in cohort 3. At data cutoff on Feb 24, 2017, median follow-up was 58·1 months (IQR 34·0–74·4) in the overall patient population, and 65·8 months (40·9–82·4) in cohort 1, 53·4 months (28·2–64·1) in cohort 2, and 76·4 months (61·2–76·5) in cohort 3. During the treatment phase, the most common grade 3 or worse adverse events were hypophosphataemia (24 [5%] of 526 patients), osteonecrosis of the jaw (17 [3%], pain in extremity (12 [2%]), and anaemia (11 [2%]). Serious adverse events were reported in 138 (26%) of 526 patients; the most common were osteonecrosis of the jaw (17 [3%]), anaemia (6 [1%]), bone giant cell tumour (6 [1%]), and back pain (5 [1%]). 28 (5%) patients had positively adjudicated osteonecrosis of the jaw, four (1%) had atypical femur fracture, and four (1%) had hypercalcaemia occurring 30 days after denosumab discontinuation. There were four cases (1%) of sarcomatous transformation, consistent with historical data. Ten (2%) treatment-emergent deaths occurred (two of which were considered treatment-related; bone sarcoma in cohort 2 and sarcoma in cohort 1). Median time to progression or recurrence for patients in cohort 1 during the first treatment phase was not reached (28 [11%] of 262 patients had progression or recurrence). 227 (92%; 95% CI 87–95) of 248 patients who received at least one dose of denosumab in cohort 2 had no surgery in the first 6 months of the study. Interpretation: The types and frequencies of adverse events were consistent with the known safety profile of denosumab, which showed long-term disease control for patients with GCTB with unresectable and resectable tumours. Our results suggest that the overall risk to benefit ratio for denosumab treatment in patients with GCTB remains favourable. Funding: Amgen.